Twenty‐five years of Review of Financial Economics: A bibliometric overview. Issue 1 (27th December 2019) - Baker, H. Kent; Kumar, Satish; Pattnaik, Debidutta
Abstract: The Review of Financial Economics ( RFE ) has published empirical research covering all areas of financial economics since 1994. It celebrated its silver jubilee year of publishing in 2018. Using bibliometric techniques, we analyze the journal's impact, its prominent topics and most prolific authors including their affiliated institutions and countries. We also identify the bibliographic couplings of authors and their affiliated institutions and countries, co‐citations of journals, and co‐occurrences of the authors' specified keywords. Our results show that about 83% of the published works receiving at least one citation between 1994 and 2018 and about 68% are co‐authored. Among the important themes discussed in RFE, the words "stock", "market, " and "risk" occupy central positions in RFE publications. Bibliographic coupling analysis identifies six clusters: (a) macroeconomic indicators, (b) investments, (c) financial institutions, (d) stock market, (e) corporate governance, and (f) corporate financial decisions.